1994
DOI: 10.1111/j.1365-2125.1994.tb04392.x
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin inhibits cellular cholesterol synthesis and increases low density lipoprotein receptor activity in macrophages: in vitro and in vivo studies.

Abstract: 1 Pravastatin, a 3-hydroxy-3-methylglutaryl coenzyme-A (HMG-CoA) inhibitor, is a highly selective inhibitor of hepatic cholesterol synthesis. We studied the in vivo and in vitro effects of pravastatin on macrophage cholesterol metabolism. 2 The effects of incubating pravastatin with human monocyte derived macrophages (HMDM), mouse peritoneal macrophages (MPM) and a J-774 A.1 macrophagelike cell line, on macrophage cholesterol synthesis, cellular degradation of native low density lipoprotein (LDL) and modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…In agreement with previous studies in human monocyte-derived macrophages, 12,13 LOV increased the receptor-specific degradation of nat LDL. This effect was observed when LOV was given to freshly seeded cells during their spontaneous differentiation to adherent macrophages, as well as in matured macrophages allowed to differentiate under control conditions before LOV treatment.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with previous studies in human monocyte-derived macrophages, 12,13 LOV increased the receptor-specific degradation of nat LDL. This effect was observed when LOV was given to freshly seeded cells during their spontaneous differentiation to adherent macrophages, as well as in matured macrophages allowed to differentiate under control conditions before LOV treatment.…”
Section: Discussionsupporting
confidence: 81%
“…12 The lower concentration of the drug used and the longer cultivation periods may explain the lack of effect in this study. On the other hand, our results are similar to the only other study on cultured human monocytes, where a 30%, but statistically insignificant, decrease in acetyl LDL degradation after a 2-day incubation with 13 mol/L mevastatin was observed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…41) In this way, it can inhibit the interaction between platelets and fibrinogen and reduce the expression of diverse agents involved in the coagulation process. 42) Pravastatin has anti-inflammatory effects, and promotes a blockade of macrophage activation 43) and the formation of foam cells. 43,44) More recently it was demonstrated that the drug promotes in vitro inhibition of PDGF and also affects the transduction intermediated by angiotensin II through the suppression of two proto-oncogenes, c-jun and c-fos, 45) indicating the possibility of inducing a regression of myocardial hypertrophy through the blockade of independent signaling in the reduction of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…42) Pravastatin has anti-inflammatory effects, and promotes a blockade of macrophage activation 43) and the formation of foam cells. 43,44) More recently it was demonstrated that the drug promotes in vitro inhibition of PDGF and also affects the transduction intermediated by angiotensin II through the suppression of two proto-oncogenes, c-jun and c-fos, 45) indicating the possibility of inducing a regression of myocardial hypertrophy through the blockade of independent signaling in the reduction of cholesterol. 46) The protection of cardiomyocytes by pravastatin in this study most likely occurred due to its action on the modulation of vascular relaxation mediated by the endothelium.…”
Section: Discussionmentioning
confidence: 99%